Cellulose, hemicellulose, lignin, and their derivatives as multi-components of bio-based feedstocks for 3D printing. (15th December 2020) - Yang, Jian; An, Xingye; Liu, Liqin; Tang, Shiyu; Cao, Haibing; Xu, Qingliang; Liu, Hongbin
Highlights: The three main components of plants act as bio-feedstocks for 3D printing. Cellulose and its derivatives based 3D bio-feedstocks are reviewed. Hemicellulose and its derivatives based 3D bio-feedstocks are reviewed. Lignin and its derivatives based 3D bio-feedstocks are reviewed. The roles, challenges and future perspectives of the three components in 3D feedstocks are underlined. Abstract: Three-dimensional (3D) printing, known as revolutionary and disruptive innovation in manufacturing technology, supports great opportunities to rapidly construct a wide range of tailored object geometries. Cellulose, hemicellulose, and lignin as the three most common natural polymers and main components of plant resources, possess great economical potential for bio-based products due to their attractive advantages. The integration of 3D printing technology involved with cellulose, hemicellulose and lignin as the major bio-based feedstock for high-performance 3D printed products has received great concern in the R&D areas. In this review, the aim is to shed light on a cutting-edge review on the most recent progress based on cellulose, hemicellulose and lignin, as well as their derivatives as multi-components of bio-feedstock for 3D printing, in which the applications, roles and functions of the plant-derived biomass for 3D printing are also highlighted. The challenges and perspectives for future work are provided, to underscore critical issues and opportunities.